2013
DOI: 10.1308/003588413x13511609956895
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of outcome of non-operative treatment of acute scaphoid waist fracture

Abstract: Fifteen per cent of acute fractures of the scaphoid waist fail to unite if treated non-operatively in plaster, resulting in persistent loss of function. Suspected risk factors for non-union include proximal fracture fragment avascularity and assessments of fracture displacement and comminution. This series of studies investigated whether one can accurately identify which scaphoid waist fractures will unite with plaster treatment. They suggest that proximal fracture fragment vascularity is not a predictor of ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 10 publications
0
14
0
2
Order By: Relevance
“…The US value in the diagnosis of irregular bone fractures, especially in scaphoid, was previously discussed [8][9][10][11][12], with the conclusion that US might be valuable even in patients without changes in CR. At the same time, other studies showed that US can depict more fractures than CR [13][14][15] and should be considered an alternative for the more expensive and less available MRI and CT.…”
Section: Bones Injuries (Fractures)mentioning
confidence: 99%
“…The US value in the diagnosis of irregular bone fractures, especially in scaphoid, was previously discussed [8][9][10][11][12], with the conclusion that US might be valuable even in patients without changes in CR. At the same time, other studies showed that US can depict more fractures than CR [13][14][15] and should be considered an alternative for the more expensive and less available MRI and CT.…”
Section: Bones Injuries (Fractures)mentioning
confidence: 99%
“…Of particular interest is fracture of the carpal scaphoid 15 23 24. When a scaphoid fracture is suspected clinically but radiographs are negative, CT or MR is often utilised to definitively diagnose the presence of a fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Davis suggests that all fractures with >3 mm displacement should be operated early to prevent the development of non-union. 7) This makes it important to differentiate early between displaced and nondisplaced fractures. Plain radiographs have only a 33% sensitivity for the diagnosis of displacement, even when scaphoid series are performed.…”
Section: Introductionmentioning
confidence: 99%